PENERAPAN METODE SNOWBAAL TRHOWING TERHADAP HASIL BELAJAR SISWA PADA MATERI HIDROSFER DI KELAS XI SMA NEGERI 14 TIDORE KEPULAUAN - Ibrahim, Djubaeda; Suaema, Andi; Halek, Dahri Hi (Jurnal Pendidikan dan Ekonomi (JUPEK), 2024)
The research objective that will be achieved in this research is the application of the snowball thowing learning model to improve student learning outcomes in hydrosphere material in class 10 of SMA Negeri 14 Tidore Islands. This type of research is classroom action research (PTK) using quantitative research methods. The subjects in this research were class XI students at SMA Negeri 14 Tidore Islands with a total of 28 students. The application of the snowball thowing learning model can improve the learning outcomes of class There has been an increase in student learning outcomes which are categorized as "good 65.89%. Meanwhile, in the second cycle test, the activation of student learning outcomes increased, which was categorized as "very good" 68.89%. This shows that the minimum completeness criteria (KKM) have been met, namely 65%. Thus, the application of the snowball throwing method can improve student learning outcomes in Geography Education learning in class XI of SMA Negeri 14 Tidore Islands.